Prehistoric quarrying in the Jizerské hory mountains - Pavel Burgert; Petr Šída; František Trampota; Václav Kachlík; Antonín Přichystal (Archeologia Polski)
In the 20 years since the important discovery of metabasite quarrying in the Jizerské hory Mountains (northern Bohemia, Czech Republic) a wealth of knowledge has been gathered on this raw material used to make Neolithic polished stone tools. A synthesis of these results now gives a more comprehensive view of how this raw material was employed in different periods and extracted directly at the source sites. The overview is at the same time a springing board for further research. Exploitation of metabasite and its widest spatial distribution was in the Linear Pottery culture (LBK; 5400–5000/4900 BC). In the post-LBK period of regionalisation, the sources of raw materials for the production of polished tools were diversified and the degree of utilisation of Jizera Mountains-type metabasite is demonstrably varied by region.